Atrial septal aneurysm–a potential cause of systemic embolism. An echocardiographic study. Issue 3 (March 1985) - Gallet, B; Malergue, M C; Adams, C; Saudemont, J P; Collot, A M; Druon, M C; Hiltgen, M
Abstract : Atrial septal aneurysm is an uncommon condition. Between 1981 and 1984 10 cases of atrial septal aneurysm were diagnosed by real time cross sectional echocardiography performed in 4840 patients. The aneurysm was associated either with mitral valve prolapse (three patients) or with atrial septal defect (three patients) or occurred in isolation (four patients, two of whom had had a previous embolic event leading to the diagnosis of atrial septal aneurysm by cross sectional echocardiography). During cross sectional echocardiography the aneurysm appeared as a localised bulging of the interatrial septum, which was best seen in the subcostal four chamber view and in the parasternal short axis view at the level of the aortic root. The aneurysm either protruded into only the right atrium (five patients) or moved backwards and forwards between the right and the left atria during the cardiac cycle (five patients). This motion pattern might be related to changes in the interatrial pressure gradient. The two patients who had had a systemic embolism were given anticoagulant treatment, but none underwent surgery. It is concluded that the true prevalence of atrial septal aneurysm might have been underestimated before the routine use of cross sectional echocardiography, that cross sectional echocardiography enables definitive diagnosis of this condition by a non-invasive technique, and that an atrial septal aneurysm should be suspected and looked for by cross sectional echocardiography after an unexplained systemic embolism.